Evaluation of the psychometric properties of the Italian version of the 10-item perceived stress scale in a sample of teachers - Messineo, Linda; Tosto, Crispino (Frontiers in Psychology, 2024)
Background. The 10-item Perceived Stress Scale is a widely used questionnaire for measuring perceived stress. Aim. This study aimed to assess the psychometric properties of the Italian version of the 10-item Perceived Stress Scale in a sample of Italian teachers during the COVID-19 pandemic. Methods. A cross-sectional study was performed. A sample of 1179 teachers of pre-primary, primary, and secondary schools anonymously completed an online questionnaire. A Confirmatory Factor Analysis was performed to compare the fit of a two-factor model against a one-factor solution of the scale. Multigroup CFA was run to test the measurement invariance of the two-factor PSS-10 solution across gender. The internal reliability of the scale was evaluated using Cronbach’s alpha and McDonald’ omega coefficients. Convergent validity with measures of subjective well-being and self-reported health was evaluated. Results. The results of the Confirmatory Factor Analysis showed that the two-factor structure of the 10-items Perceived Stress Scale provided a better fit to the data and supported the adequacy of the Italian version of the scale. The two-factor model showed measurement invariance across female and male groups, as result of the multigroup CFA. The scale proved to have good internal reliability. Correlation analyses with measures of the Positive Affect and Negative Affect Schedule and self-reported health supported convergent validity. Conclusions. These results suggest that the Italian version of the 10-item Perceived Stress Scale has good psychometric properties and can be considered a valid and reliable instrument to assess perceived stress